(untitled) (Actualizaciones en Sida e Infectología, 2024)
Objective: To identify the Candida species isolated in female patients of reproductive age with vaginal candidiasis. To determine the antifungal (ATF) sensitivity profile of the isolated Candida species. Materials and methods: Cross-sectional descriptive study, in which 124 Candida strains from vaginal discharge samples obtained during the period from May 2022 to January 2023 were isolated in Sabouraud medium supplemented with glucose. CHROMagar Candida was used for species identification and complementary tests such as germ tube and pseudohyphae formation in human serum pool, chlamydoconidia development in corn meal agar with Tween 80 medium and investigation of trehalose assimilation were performed. In vitro sensitivity was investigated by diffusion method with ATF discs (Neo-Sensitabs®; Rosco Diagnóstika) fluconazole (FLU), itraconazole (ITRA) and amphotericin B (AMB) and following Clinical & Laboratory Standard Institute (CLSI) recommendations. Results: C. albicans was observed in 85.5% of the isolates followed by C. glabrata with 7.3%, C. krusei 4%, C. tropicalis 2.4% and other Candida species. For FLU, 0.9% of C. albicans, 11.1% of C. glabrata and 100% of C. krusei isolates showed resistance. For ITRA, 17% of C. albicans isolates, 55.6% of C. glabrata and 100% of C. krusei were resistant. There were no isolates resistant to AMB. Conclusions: Vaginal candidiasis continues to present Candida albicans as the main etiological agent, which is widely sensitive to ATFs. C. glabrata and C. krusei species show increased resistance to azoles and are often responsible for ATF treatment failures. The results obtained ratify the growing need for Candida species identification tests and determination of in vitro sensitivity to ATFs in order to guide the treatment of vaginal candidiasis towards therapeutic success.